2022
DOI: 10.1177/2050313x211072663
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel obstruction precipitated by intussusception of Meckel’s diverticulum

Abstract: Small bowel obstruction (SBO) secondary to intussusception of Meckel’s diverticulum (MD) is a rare cause of acute abdominal pain that may warrant urgent surgical treatment. Volvulus or intussusception of the small bowel with presence of MD as the lead point is the most commonly reported etiology of Meckel’s related obstructions. We report an interesting case of a small bowel obstruction caused by the intussusception of an MD within its own lumen. The case involves a 30-year-old male who presented to the emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The literature search in our search was conducted using the terms(s): “small bowel obstruction” AND “meckel's diverticulum” OR “diverticulitis” OR “volvulus” OR “intussusception”. The symptomatology, imaging findings, treatment employed, and the follow-up are delineated by Table 1 below [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search in our search was conducted using the terms(s): “small bowel obstruction” AND “meckel's diverticulum” OR “diverticulitis” OR “volvulus” OR “intussusception”. The symptomatology, imaging findings, treatment employed, and the follow-up are delineated by Table 1 below [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ].…”
Section: Discussionmentioning
confidence: 99%
“… Exploratory laparotomy Alive, no complications The diverticulum was resected using a GIA stapler, without small bowel resection lower quadrant and suprapubic pain and several episodes of vomiting without flatus. Zorn et al [ 53 ] 2022 30 M Abd & chest X-ray. CT of Abd Showed dilated loop sof small bowel and a distal high-grade SBO with multiple dilated loops of small bowel throughout the abdomen measuring up to 3.5 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the literature, children up to 10 years of age represent more than 50% of symptomatic MD cases, ( 3 ) the incidence in the reports reviewed in this discussion proved to be slightly different. Two patients were less than 6 months of age, ( 6 , 10 ) three between 1 and 6 years of age, ( 14 , 16 , 17 ) five between 15 and 30 years of age ( 5 , 7 , 13 , 18 , 19 ) and five between 40 and 50 years of age. ( 8 , 9 , 11 , 12 , 15 )…”
Section: Discussionmentioning
confidence: 99%
“…From a geographical perspective, we observed that 15 publications came from five continents. One was from America (United States), (5) four from Europe (Italy, (6) France, (7) Spain (8) and the United Kingdom), (9) one from Africa (Tunisia), (10) seven from Asia (Japan, (11)(12)(13)(14) South Korea, (15) China (16) and Syria) (17) and two from Oceania (Australia). (18,19) Regarding the age of the patients included in this sample, there was a range from newborns to 49 years of age.…”
Section: Epidemiologymentioning
confidence: 99%
“…Some authors document that resection of the segment of the bowel that contains the diverticulum followed by primary anastomosis is preferable to wedge resection or tangential mechanical stapling due to the risk of leaving behind an abnormal heterotopic mucosa. [ 4 , 5 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%